A randomized, double‐blind, placebo‐controlled, multicenter, parallel‐group study to evaluate the efficacy and safety of adjunctive brivaracetam in adult patients with uncontrolled partial‐onset seizures. (16th October 2015) - Klein, Pavel; Schiemann, Jimmy; Sperling, Michael R.; Whitesides, John; Liang, Wei; Stalvey, Tracy; Brandt, Christian; Kwan, Patrick
Summary: Objective: Brivaracetam (BRV), a selective and high‐affinity synaptic vesicle protein 2A ligand, is in development as adjunctive treatment for partial‐onset (focal) seizures (POS). This phase 3 study (N01358; NCT01261325) aimed to confirm the efficacy and safety/tolerability of BRV in adults (≥16–80 years) with POS. Methods: This randomized, double‐blind, placebo‐controlled, multicenter study enrolled patients with uncontrolled POS despite ongoing treatment with 1–2 antiepileptic drugs. Patients exposed to levetiracetam ≤90 days before visit 1 were excluded. Patients entered an 8‐week prospective baseline period, followed by a 12‐week treatment period when they were randomized 1:1:1 to placebo (PBO), BRV 100 mg/day, or BRV 200 mg/day, started without up‐titration. The co‐primary efficacy outcomes were percent reduction over placebo in 28‐day adjusted POS frequency, and ≥50% responder rate based on percent reduction in POS frequency from baseline to the treatment period. Results: Seven hundred sixty‐eight patients were randomized; 760 were included in the efficacy analysis: 259, 252, and 249 in PBO, BRV 100 mg/day, and BRV 200 mg/day groups, respectively. Percent reduction over PBO in 28‐day adjusted seizure frequency (95% confidence interval [CI]) was 22.8% for BRV 100 mg/day (13.3–31.2%; p < 0.001) and 23.2% for BRV 200 mg/day (13.8–31.6%; p < 0.001). The ≥50% responder rate (odds ratio vs. PBO; 95% CI) was 21.6% for PBO, 38.9% for BRV 100 mg/day (2.39; 1.6–3.6; p < 0.001), and 37.8% for BRV 200 mg/day (2.19; 1.5–3.3; p < 0.001). Treatment‐emergent adverse events (TEAEs) occurred in 155 (59.4%) of 261 PBO patients versus 340 (67.6%) of 503 BRV‐treated patients (safety population). Discontinuation rates due to TEAEs were 3.8%, 8.3%, and 6.8% for PBO, BRV 100 mg/day, and BRV 200 mg/day, respectively. Most frequent TEAEs (PBO versus BRV) were somnolence (7.7% vs. 18.1%), dizziness (5.0% vs. 12.3%), and fatigue (3.8% vs. 9.5%). Significance: Adjunctive BRV 100 and 200 mg/day was efficacious in reducing POS in adults without concomitant levetiracetam use and was well tolerated.